The Influence of Outdoor Learning Method on Student Achievement in Fiqh Subject at Madrasah Tsanawiyah Muhammadiyah 06 Sambi Simo Boyolali - Hanik, Asifak Umi; Abbas, Ngatmin; Hidayat, M. Yunan (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2025)
Traditional classroom settings often limit student engagement in Islamic jurisprudence (Fiqh) education, potentially affecting learning outcomes. Outdoor learning presents an alternative approach that may enhance student achievement through experiential learning. This study aims to determine the influence of outdoor learning methods on student achievement in Fiqh subject at Madrasah Tsanawiyah Muhammadiyah 06 Sambi. This research employed an experimental design with 15 seventh-grade students as the experimental group receiving outdoor learning intervention and 10 seventh-grade students as the control group with conventional learning. Student achievement was measured using questionnaires administered in pre-cycle, first cycle, and second cycle phases. The findings revealed significant improvements in student achievement. Pre-cycle assessment showed 51.5% achievement, which increased to 68.9% in the first cycle, representing a 17.04% improvement. Implementation of the second cycle resulted in 85.04% achievement, demonstrating an additional 16.50% improvement from the first cycle. The substantial incremental gains confirm the positive influence of outdoor learning methods on enhancing student achievement in Fiqh subjects. This research highlights the importance of experiential and contextual learning approaches in Islamic education settings. Educators should consider incorporating outdoor learning strategies into Fiqh curriculum to improve student engagement and academic performance in Islamic jurisprudence education.Setting kelas tradisional sering membatasi keterlibatan siswa dalam pendidikan hukum Islam (Fiqih), yang berpotensi mempengaruhi hasil belajar. Pembelajaran luar ruangan (outdoor learning) menyajikan pendekatan alternatif yang dapat meningkatkan prestasi siswa melalui pembelajaran berbasis pengalaman. Penelitian ini bertujuan untuk menentukan pengaruh metode outdoor learning terhadap prestasi belajar siswa pada mata pelajaran Fiqih di Madrasah Tsanawiyah Muhammadiyah 06 Sambi. Penelitian ini menggunakan desain eksperimental dengan 15 siswa kelas VII sebagai kelompok eksperimen yang menerima intervensi pembelajaran luar ruangan dan 10 siswa kelas VII sebagai kelompok kontrol dengan pembelajaran konvensional. Prestasi belajar siswa diukur menggunakan angket yang diadministrasikan dalam tahap prasiklus, siklus pertama, dan siklus kedua. Temuan menunjukkan peningkatan signifikan dalam prestasi belajar siswa. Penilaian prasiklus menunjukkan prestasi 51,5%, yang meningkat menjadi 68,9% pada siklus pertama, menunjukkan peningkatan sebesar 17,04%. Implementasi siklus kedua menghasilkan prestasi 85,04%, mendemonstrasikan peningkatan tambahan sebesar 16,50% dari siklus pertama. Peningkatan bertahap yang substansial ini mengkonfirmasi pengaruh positif metode outdoor learning terhadap peningkatan prestasi belajar siswa pada mata pelajaran Fiqih. Penelitian ini menekankan pentingnya pendekatan pembelajaran eksperiensial dan kontekstual dalam lingkungan pendidikan Islam. Pendidik sebaiknya mempertimbangkan untuk mengintegrasikan strategi pembelajaran luar ruangan ke dalam kurikulum Fiqih untuk meningkatkan keterlibatan siswa dan kinerja akademik dalam pendidikan hukum Islam.